Load Frequency Control of Renewable Energy Power Systems Based on Adaptive Global Fast Terminal Sliding Mode Control - Jiaming Qian; Xinxin Lv (Applied Sciences, 2025)
In this paper, the load frequency control (LFC) of multi-area power systems incorporating photovoltaic (PV) and energy storage systems (ESSs) is studied. First, the model of the LFC system encompassing PV and ESS is established. Then, a novel LFC scheme based on adaptive global fast terminal sliding mode control (AGFTSMC) is proposed. To make the system robust globally, an adaptive sliding mode control law and a new type of global fast terminal sliding mode surface containing a nonlinear time-varying function are designed. Moreover, by utilizing the improved Lyapunov function, the stability of the system is analyzed. Finally, two simulation experiments incorporating the two-area LFC system and IEEE 39-bus test power system are presented to validate the effectiveness of the proposed method. The simulation results show that adopting the AGFTSMC can significantly reduce steady-state error and stabilization time. This makes it a promising solution for maintaining frequency stability.